Government Capital, Intimate and Community Social Capital, and Food Security Status in Older Adults with Different Income Levels1. (5th August 2014) - Dean, Wesley R.; Sharkey, Joseph R.; Nalty, Courtney C.; Xu, Jin
Abstract Whether government‐based forms of food assistance such as the Supplemental Nutrition Assistance Program (SNAP), communal efforts including food pantries, aid from friends and family, or alternative means such as gardening are the appropriate means to reduce the prevalence of household food insecurity is a continuous source of policy contention. To inform this debate, we examine the relative importance of these forms of food assistance and acquisition to a sample of U.S. older adults from the 2010 Brazos Valley Health Assessment of central Texas households that have been stratified by income eligibility for SNAP, low‐income SNAP ineligibility, and above low income status. To identify how membership in these socioeconomic groups constrains household capacity to acquire sufficient food to maintain an adequate and healthy diet, we explore the varied associations of assets received from government; communal and intimate social networks; and alternative food sources such as gardening, hunting, and fishing with household food security across socioeconomic status, while examining the importance of place of residence on the use of capital assets. SNAP participation was the only specific capital asset associated with all levels of food insecurity for both SNAP‐eligible and ineligible low‐income groups, thus emphasizing the continued importance of food assistance among poverty‐level older adults.